Mean Length of Stay of Orthopedic Trauma Patients Admitted in the Intensive Care Unit of a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Pradhan, Ishor; Regmi, Subhash; Joshi, Mohan Chandra; Chaudhary, Rajesh Kumar; Banskota, Bibek; Joshi, Amit (Nepal Orthopaedic Association Journal, 2023)
Introduction: Audit of intensive care unit admissions is an important tool in monitoring and improving quality of health service provided. Length of stay in the intensive care unit provides key information to health care service providers regarding the burden of major orthopedic trauma and helps in improving treatment policies. Hence, this study aims to find out the mean length of stay among orthopedic trauma patients admitted in the intensive care unit of a tertiary care center.Methods: A descriptive cross-sectional study was carried out among orthopedic trauma patients admitted to the intensive care unit between January 1, 2022, and December 31, 2022, following ethical clearance from institutional review committee of B.&B. Hospital Gwarko, Lalitpur, Nepal (reference no: B&BIRC-23-09). All orthopedic trauma patients admitted in the intensive care unit were included. Clinical records with missing information and patients who had repeat admissions due to other issues were excluded. Data were collected retrospectively. Convenient sampling method was used. Point estimate and 95% confidence interval were calculated. Results: Mean length of stay of orthopedic trauma patients admitted in intensive care unit was 4.68±5.01 days (3.89-5.47, 95% confidence interval). Mean age of the patients was 42.07±21.76 years, and 118 (76.62%) were males and 36 (23.38%) were females.Conclusion: The mean length of stay of orthopedic trauma patients admitted in the intensive care unit of a tertiary care center was lower to that reported in other international studies.